Gambaran Kadar Perak (Ag) Pada Limbah Cair Fixer Di Instalasi Radiologi Rumah Sakit Pertamedika Ummi Rosnati Banda Aceh - Pocut Zairiana Finzia; Dewi Febriyanti; Adam S (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
A study on the description of silver (Ag) levels in liquid waste fixer originating from a radiology installation before being processed at the Waste Treatment Installation is sometimes necessary to avoid environmental pollution. The time and place of this research were conducted at the radiology installation for approximately 1 (one) month. The purpose of this writing is to determine the description of the silver (Ag) levels of fixer in the radiology installation. This research method is field observation. and the processing of silver levels was carried out at the Medan standardization research agency (baristand) with researchers sending samples of 100 mg/l to be tested for silver levels. The thing studied in this study was to determine the description of silver levels using the Atomic Absorption Spectrophotometry (AAS) method. From the observation results after processing, the Ag content was 0.03 mg/L. After processing, the silver content was allowed to be discharged directly into the environment or public channels because the results were still below the established quality standards, namely 5.0 mg/L. However, it would be better if each hospital was advised to process the liquid waste at the Wastewater Treatment Plant to avoid environmental pollution.